Ethical Dilemmas: Unveiling Accounting Students' Whistleblowing Intentions in Indonesian University - Suhartini, Dwi; Putri, Sofie Yunida; Azmiyanti, Rizdina (Universitas Syiah Kuala, 2024)
Objective This study examines the impact of professional commitment and Machiavellian traits on whistleblowing intentions among accounting students in A-accredited universities in Surabaya, Indonesia.Design/methodology Using non-probability quota sampling, 150 questionnaires were collected through Google Forms. Data analysis employed multiple linear regression and independent sample t-tests.Results Results show that professional commitment and Machiavellian traits significantly influence students whistleblowing intentions. No significant differences between public and private university students regarding these factors were found. The study reveals high levels of professional commitment and Machiavellian traits among accounting students, emphasizing the need for business ethics education to promote integrity in the accounting profession. Universities should implement strategies to control Machiavellian traits through incentives and punishments for addressing campus fraud. The research highlights the importance of ethics education in strengthening resolve against corruption and ethical violations in accounting.Research limitations/implications Limitations include potential variations in reporting intentions upon entering the workforce due to factors like reporting costs and employment opportunities.NoveltyThe studys conclusions relate only to new graduates, and non-probability sampling means results cannot be generalized to all situations or applied to individuals with substantial work experience.